Psychological Well-Being Profile: The Role of Gratitude and Social Support for Parents with Children with Special Needs - Laili, Nurfi; Fahmawati, Zaki Nur; Wisyastuti, Wdiyastuti; Affandi, Ghozali Rusyid (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2022)
The parenting style in the family is built on the readiness of parents. Parents with children with special needs must have a good understanding of their children's condition. Children with special needs are a condition of a child who has different needs from other normal children. Of course, this special needs condition makes the child need a special parenting style from their parents. This makes parents expected to continue to have good psychological well-being in caring for children with special needs. The subjects of this research are parents who have children with special needs and attend special schools with a total of 54 people. The results of the study were analyzed using regression data analysis techniques. The analysis showed that the research hypothesis was accepted: that gratitude and social support could affect psychological well-being (F = 5.731; sig. 0.006 < 0.05). This study concludes that gratitude and social support affect 18.4% of psychological well-being, and the rest is influenced by other variables not examined.